PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP PROFITABILITAS - Muhammad Soedarman; Ilham Mochtar; Triana Murtiningtyas (MEASUREMENT : Jurnal Program Studi Akuntansi, 2023)
This research aims to examine the influence of Good Corporate Governance and leverage on profitability. In this research, the Good Corporate Governance variable is measured by the board of directors, independent commissioners and audit committee, while the leverage variable is measured by the Debt to Equity Ratio (DER). This type of research is quantitative research because it uses an approach that emphasizes data analysis. The sampling technique used a purposive sampling method, namely the researcher determined the sample based on predetermined criteria and obtained a sample of 186 data from 62 companies in the basic industrial and chemical sectors listed on the Indonesia Stock Exchange (BEI) during the 2020-2022 period. The analytical methods used are descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results show that the audit committee has no effect on profitability, independent commissioners have a positive and significant effect on profitability, the board of directors has a positive and significant effect on profitability, and leverage has a positive and significant effect on profitability